Examining the role of Rh/Si cooperation in alkene hydrogenation by a pincer-type [P2Si]Rh complex. Issue 24 (2nd February 2016) - Whited, Matthew T.; Deetz, Alexander M.; Donnell, Theodore M.; Janzen, Daron E.
Abstract : A bis(phosphine)/triflatosilyl pincer-type Rh(i ) complex can reversibly store one equivalent of H2 across the Si–Rh bond upon triflate migration from silicon to rhodium. Abstract : A bis(phosphine)/triflatosilyl pincer-type Rh(i ) complex can reversibly store one equivalent of H2 across the Si–Rh bond upon triflate migration from silicon to rhodium. The triflatosilyl complex serves as an effective precatalyst for norbornene hydrogenation, but Si–OTf bond cleavage is not implicated in the major catalytic pathway. The combined findings suggest possible strategies for M/Si cooperation in catalytic processes.